Espiritualidade e estratégias de enfrentamento de pessoas em tratamento oncológico - Garcia, Viviane Cristina Bianchi (2021)
Religious/spiritual support has been a relevant coping strategy used by patients to better adjust to the new illness situation. Some beneficial effects of using Spiritual-Religious coping (SRC) strategies are related to greater adherence to treatment, easier access to social support networks, generation of meaning and purpose in life, optimism and reduction of depressive and anxious symptoms. Objectives: to evaluate and compare the spiritual dimension of patients undergoing cancer treatment. Method: this is a cross-sectional quantitative study, with descriptive correlational research. A sample composed of 259 adult male and female patients undergoing treatment, admitted to the oncology ward and chemotherapy sector of a large teaching hospital in the interior of the state of São Paulo, was eligible for convenience. The instruments used were: socio-demographic data questionnaires; hospital anxiety and depression scale - HADS; Herth Hope Scale - HHS; and short scale of religious confrontation. Patients were approached during hospitalization and chemotherapy sessions and after invitation, reading and signing the Informed Consent Form, the collection was carried out individually as an interview. In the inferential statistical analysis of the quantitative variables, the Kolmogorov-Simirnov test was used to verify the normality of the data, and the Kruskal-Wallis test to compare non-parametric data. Correlation analyzes were performed using Pearson and Spearman correlation tests. Results: the main findings pointed to a positive correlation between the Positive Spiritual-Religious coping (PSRC) and the sociodemographic aspects: sex (r=0.143; p<0.05) and frequency in religious ceremonies (r=0.2032; p<0.05), weak positive correlation between the Negative Spiritual-Religious coping (NSRC) and the clinical aspect: time of diagnosis (r=0.1251; p<0.05); negative relationship between positive spiritual religious coping (PSRC) and indicators of anxiety (r=-0.2726; p<0.0001) and depression (r=-0.3493; p<0.0001); positive correlation between negative spiritual religious coping (NSRC) and indicators of anxiety (r=0.339; p<0.0001) and depression (r=0.332; p<0.0001); moderate positive correlation between hope indicators and PSRC (r=0.455; p<0.0001) and negative correlation between hope indicators and NSRC (r=-0.289; p<0.0001). Conclusion: this paper established significant correlations regarding PSRC and NSRC, with sociodemographic data (sex; frequency in religious ceremonies), clinical (time of diagnosis) and psychosocial (anxiety; depression) variables and with hope indicators. The results of the analyzes indicate that R/S is a dimension practiced and present in the daily lives of people evaluated as a manifestation of spirituality, regardless of religion or belief. Studies based on the current theme argue that the practice of PSRC directly impacts the health-disease process, being considered as crucial in the context of serious or terminal illness. In addition, it acts as a facilitator in promoting a reframing of a difficult experience. The need for qualitative research on the perception of individuals who are undergoing cancer treatment about possible benefits and difficulties that lead to the use of SRC becomes evident as complementarity and enrichment of data.